Evaluation of the Implementation of the Hospital Management Information System Using the Hot-Fit Method - Tania Evita Salsabila; Shela Julia Veronica (GLOBAL HEALTH SCIENCE GROUP, 2024)
Implementing a hospital management information system (SIMRS) is very important to integrate all information generated in the service process. SIMRS can encourage increased efficiency and effectiveness of services in hospitals along with the smooth flow of information between service providers and patients. In the long term, the projected use of SIMRS can save costs and avoid repetitive administrative activities. The aim of this research is to determine the level of SIMRS utilization at RSU Hermina Tangerang and to determine the factors that influence SIMRS utilization. The type of research used in this research is quantitative with a cross-sectional research design using a survey approach. The research population is all employees who use SIMRS who have a username. Data collection was carried out using a questionnaire. Data analysis using SEM PLS. Based on the research results, it shows that SIMRS at RSU Hermina Tanggerang is not running optimally, it is evident that there are still many obstacles occurring in the field.